Mycobacterial Lipoprotein Z Triggers Efficient Innate and Adaptive Immunity for Protection Against Mycobacterium tuberculosis Infection - Chen, Yingying; Xiao, Jia-ni; Li, Yong; Xiao, Yang-jiong; Xiong, Yan-qing; Liu, Ying; Wang, Shu-jun; Ji, Ping; Zhao, Guo-ping; Shen, Hao; Lu, Shui-hua; Fan, Xiao-yong; et al. (Frontiers in Immunology, 2019)
Mycobacterial lipoproteins are considered to be involved in both virulence and immunoregulatory processes during Mycobacterium tuberculosis (M.tb) infection. In our previous investigations on the immunoreactivity of more than 30 M.tb proteins in active TB patients, we identified mycobacterial lipoprotein Z (LppZ) as one of the most immune dominant antigens. How LppZ triggers immune responses is still unclear. In this study, we analyzed LppZ-mediated innate and adaptive immunity using a murine air pouch model and an M.tb infection model, respectively. We found that LppZ could not only recruit inflammatory cells but also induce the production of proinflammatory cytokines inside the pouches. LppZ could also induce strong Th1 responses following immunization and confer protection against challenge with M.tb virulent strain H37Rv at a similar level to BCG vaccination but with less pathological damage in the lungs. Furthermore, we revealed the presence of LppZ-specific functional CD4+ T cells in the lungs of the challenged mice that were capable of secreting double or triple cytokines, including IFN-γ, IL-2 and TNF-α. Our study thus demonstrates that LppZ is of strong immunogenicity during M.tb infection in both humans and mice and has the ability to trigger effective innate and cellular immunity. Considering the limitations of candidate antigens in the pipeline of TB vaccine development, LppZ-mediated immune protection against M.tb challenge in the mouse model implies its potential application in vaccine development.